Desarrollo de la conciencia fonológica del lenguaje en niños del sub nivel 2 de la “Unidad educativa Francisco Huerta Rendón” mediante los juegos didácticos - Parra Guapulema, Nathaly (2021)
The purpose of this research work is to inform and motivate the use of didactic games in the teaching-learning process of boys and girls of Initial Education in order to achieve an optimal development of phonological awareness. The research carried out was born as a need to know how playful activities generate a positive effect on learning phonemes, the development of this research occurs due to the fact that a low level of motivation has been observed in children during hours classes in which content related to language is taught. Several interviews were carried out with parents and teachers to learn more about their feelings towards the academic performance of children regarding the recognition of the sounds and spellings of phonemes, reaching the conclusion that there is a need for didactic methods s to properly develop phonological awareness.